THE EFFECTS OF SYSTEM PARAMETERS ON THE INCEPTION OF FLASHING USING RELAP5 : Received: 29th June 2021; Revised: 14th July 2022, 21st July 2022, 1st August 2022; Accepted: 02nd August 2022 - Bello, Mary Olubunmi; Minjun, Peng; Genglei, Xia (MATTER: International Journal of Science and Technology, 2022)
Natural circulation systems (NCS) are prone to instabilities, they are more unstable compared to forced circulation systems as a result of the low driving head and nonlinearity of the system. Flashing instability is prominent in these systems at low pressure due to the presence of a long nonheated riser to enhance the driving force. RELAP5 code has been identified as one of the Best Estimate (BE) codes used in the analysis of the systems. The studies by different authors showed that the effects of system parameters on instability generally have gained the attention of researchers in recent years. However, these studies have not discussed how these parameters prevent or enhance the commencement of flashing instability. This we sought to achieve in this work, by zeroing in on the inception of flashing instability, by comparing what happened at different heat fluxes. The objective of this work is to investigate the effects of system parameters on the inception of flashing instability in a natural circulation system using the RELAP5 code. With the increase in inlet subcooling and height of the riser, flashing moved to the outlet of the riser, stabilizing the system. However, an opposite effect was observed with an increase in the inlet resistance.